PcNAC25, a NAC transcription factor of Pugionium cornutum(L.) Gaertn conferring enhanced drought and salt stress tolerances in Arabidopsis - Zhaoxin Wu; Ping Wang (Scientific Reports)
Abstract Pugionium cornutum (L.) Gaertn (P. cornutum) has strong tolerance to drought, salt and disease, but the tolerance mechanisms for such stresses in P. cornutum are largely unknown. In this study, we identified the PcNAC25 transcription factor gene in P. cornutum. Its open reading frame was revealed to comprise 891 bp, encoding a protein consisting of 297 amino acids, with an isoelectric point of 6.61. Phylogenetic analysis showed that PcNAC25 was most closely related to ANAC019. The expression of PcNAC25 was induced by dehydration, mannitol, heat, cold, salt stresses and abscisic acid (ABA), salicylic acid (SA), and methyl jasmonate (JA) treatments. A subcellular localization analysis confirmed that PcNAC25 was localized in the nucleus. The overexpressing PcNAC25 lines in Arabidopsis had longer roots than wild-type (WT) lines under drought and salt stress. The overexpression of PcNAC25 improved drought and salt tolerance in transgenic Arabidopsis. Under drought and salt stress, PcNAC25 transgenic lines exhibited higher the CAT, POD and SOD activities and scavenging ability of hydroxyl radical than WT, more proline accumulation than WT and less MDA and H2O2 content and superoxide anion production rate than WT. PcNAC25 transgenic lines also exhibited greater reduced water loss rate of detached leaves than WT. Meanwhile, DAB and NBT staining showed that the accumulation of hydrogen peroxide and superoxide anion in PcNAC25 transgenic lines were also less than WT. In addition, overexpressing PcNAC25 enhanced the expression of drought response genes (DREB2A, SOD4, RD29A, NCED3, POD3, P5CS1, PYR1 and SAG13) and salt response genes NHX, SLAH1, SOS1 and NPF6.3. The mentioned above results indicated that PcNAC25 is a positive regulator that activates ROS-scavenging enzymes and enhances root formation in Arabidopsis, which provided a basis for further research on the molecular mechanism of PCNAC25-mediated regulation of drought and salt stress, and also provided gene resources of drought and salt tolerance.